Aspek Yuridis Klaim Asuransi Kesehatan oleh Tertanggung: Studi Pada PT. Prudensial Cabang Medan - suhaila zulkifli; Tajuddin Noor (Jurnal Hukum Lex Generalis, 2025)
This research uses the normative juridical method by examining the laws and regulations in the field of insurance as well as the policy provisions of PT Prudential Life Assurance Indonesia. The results of the study show that PT Prudential applies two health insurance claim settlement mechanisms, namely individual claims and collective claims, each of which is subject to the terms and procedures set out in the policy. Normatively, the company is obliged to provide health protection to insurance participants, but the effectiveness of this protection is highly dependent on the fulfillment of the rights and obligations of participants in accordance with applicable regulations. In practice, there are often obstacles in the form of claim rejection due to document completeness, late reporting, or participant ignorance of the contents of the policy. This research highlights the importance of legal protection for the insured so as not to be harmed by unilateral provisions in the policy. The novelty of this research lies in the normative analysis of the imbalance of legal positions between insurance companies and participants in the claims process, which can lead to legal uncertainty. Therefore, it is necessary to strengthen regulations that guarantee justice and legal certainty for insurance participants in filing health claims.